2009
DOI: 10.1590/s0100-204x2009001100006
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature impact on photosynthetic parameters of coffee genotypes

Abstract: The objective of this work was to evaluate photoprotective mechanisms related to low positive temperatures in Coffea canephora (Conilon clones 02 and 153) and C. arabica ('Catucaí' IPR 102) genotypes, involved in cold temperature tolerance. To accomplish this, one-year-old plants were successively submitted to: temperature decrease of 0.5ºC day-1, from 25/20ºC to 13/8ºC; a three-day chilling cycle at 13/4ºC; and a recovery period of 14 days (25/20ºC). During the experiment, leaf gas exchange, chlorophyll a flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
50
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 31 publications
10
50
0
3
Order By: Relevance
“…This fact confirms the trend found in this study, where the late ripening clone group was often more productive under low temperature conditions, compared to early ripening clones. It is also noteworthy that C. arabica was better than C. canephora in practically all physiological and biochemical characteristics when subjected to low temperatures (Partelli et al, 2009;Scotti-Campos et al, 2014, Ramalho et al, 2014.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…This fact confirms the trend found in this study, where the late ripening clone group was often more productive under low temperature conditions, compared to early ripening clones. It is also noteworthy that C. arabica was better than C. canephora in practically all physiological and biochemical characteristics when subjected to low temperatures (Partelli et al, 2009;Scotti-Campos et al, 2014, Ramalho et al, 2014.…”
Section: Resultsmentioning
confidence: 93%
“…Regarding ripening time, Partelli et al (2009) observed in C. canephora clones a higher CO 2 assimilation rate and increased respiratory activity and starch accumulation in late ripening (clone 153) compared with early ripening (clone 02), when subjected to low temperatures.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Ademais, esses fatores acarretam redução da condutância estomática, da fotossíntese líquida, da eficiência fotoquímica do fotossistema II, do transporte tilacoidal de elétrons, da atividade enzimática, bem como o metabolismo do carbono, alterando ainda a composição e a estrutura dos complexos de pigmentos fotossintéticos, classes lipídicas e ácidos graxos com intensidades distintas entre genótipos e espécies (RAMALHO et al, 2003, SILVA et al, 2004, PARTELLI et al, 2009, PARTELLI et al, 2010a.…”
Section: Introductionunclassified